Peran Konseling Online dalam Mengatasi Competent Tasks Siswa di Tengah Pandemi Covid-19 - Maynawati, Aldila (IPTPI Surakarta, 2020)
The impact of the corona virus disease (Covid-19) requires several local governments to decide on implementing policies to dismiss student activities at school and implement online learning or distance learning systems. This government policy has been effectively implemented in various regions in Indonesia since March 2020, including in Sukoharjo district. The goal of this research is to investigate how the role of the counseling assistance service is, namely classical guidance in fostering student learning motivation to increase academic achievement amid the Covid-19 pandemic which is held in class XI-IPS 3 SMA N 3 Sukoharjo. This research uses interview and observation data collection techniques. The results showed a decrease in student kompeten tasks during online learning because students had difficulty understanding the material provided, lazy to carry out online learning because they felt boring. However, after online counseling was carried out students competent bags began to grow again, which was shown by students getting excited about taking online learning after joining online counseling services, and students being more disciplined in collecting assignments or homework (PR)